Aqueous - organic phases separation by membrane reactors in biodesulfurization reactions - Berdugo, Claudia; Caballero, Rocío; Godoy, Rubén Darío (CT&F - Ciencia, Tecnología y Futuro, 2002)
This work presents a membrane bioreactor prototype used to separate emulsion phases formed in the biodesulfurization reaction. Hydrophobic membranes used for the construction of the prototype allow the separation of the organic/watery phases. The separation unit resembles a tube and carcass heat exchanger. By feeding the emulsion through the housing and due to the pressure gradient pushed on the membrane, the organic phase pass through and allow to obtain an organic phase free of cells and water. Several organic phase/watery phase ratios and many cellular concentrations were evaluated. Results indicate that is possible to separate the phases by manipulating the fluid pressure within the bioreactor. This is possible even for cellular concentrations of the order of 7 g/l. The system can also be used as a reaction unit. The biological conversion was evaluated by verifying the presence of 2-HBP, one of the metabolites of the path 4S in the biodesulfurization reaction. This bioreactor configuration has not been explored before for the biodesulfurization process and therefore it represents an innovation in this research area.